1995
DOI: 10.1148/radiology.195.1.7892454
|View full text |Cite
|
Sign up to set email alerts
|

Dialysis access grafts: anatomic location of venous stenosis and results of angioplasty.

Abstract: Performance of serial venous angioplasty procedures may help prolong the life of a graft, but the patency rates diminish with subsequent interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
171
1
10

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 339 publications
(191 citation statements)
references
References 0 publications
5
171
1
10
Order By: Relevance
“…For the past 4 decades, neointimal graft hyperplasia has been a well-known entity (5), and it is generally considered the leading cause of pVA stenosis (6), mainly observed at the prosthetic-venous anastomosis (in 58% of cases) (7). Finally, it is well documented that pVAs are more prone to thrombosis than autogenous vascular access (8).…”
Section: Discussionmentioning
confidence: 99%
“…For the past 4 decades, neointimal graft hyperplasia has been a well-known entity (5), and it is generally considered the leading cause of pVA stenosis (6), mainly observed at the prosthetic-venous anastomosis (in 58% of cases) (7). Finally, it is well documented that pVAs are more prone to thrombosis than autogenous vascular access (8).…”
Section: Discussionmentioning
confidence: 99%
“…Early studies reported low incidence of inflow artery stenosis, and it is venous problems that have drawn most of the attention in the treatment of access dysfunction. 1,4 More recent studies have suggested that the incidence of inflow stenoses can be substantially high, from 28% to 35%. However, most of the inflow stenoses reported were located at the arteriovenous anastomosis rather than in the native artery.…”
Section: Discussionmentioning
confidence: 99%
“…Stenosis plagues both types of arteriovenous conduits, although PTFE grafts are more prone to such complication. In PTFE grafts, stenosis develops commonly around the graft-venous anastomosis, and less frequently at the graftarterial anastomosis [1]. In native fistulae, stenosis occurs in both the outflow vein as well as the inflow artery.…”
Section: Pathology Of Neointimal Hyperplasia In Vascular Accessmentioning
confidence: 99%
“…In hemodialysis arteriovenous grafts, the patency rate diminishes progressively over time with each angioplasty procedure. In one study, the 360-day primary patency rate of forearm PTFE loop grafts was 40% following the first angioplasty, but dropped to 25% after the second angioplasty [1]. The 180-day patency rate following the third angioplasty was 0%.…”
Section: Pathogensis Of Neointimal Hyperplasia In Vascular Accessmentioning
confidence: 99%